Symmetry of a partially-ligated state maintained by dynamics in a negatively cooperative system - Strawn, Rebecca; Murthy, Parvathi S.; Ettrich, Rüdiger H.; Pelczer, István; Carey, Jannette (Frontiers in Biophysics, 2024)
Symmetry was a key concept underlying the MWC model for allostery advanced in 1965 by Monod, Wyman, and Changeux. The reciprocal interactions of symmetrically-arranged identical subunits were proposed to stabilize multimeric assemblies together with the free energy from bound ligands that progressively favor a monomer-like state. Structural symmetry of subunits was assumed to be maintained in the partially-ligated states, even if ligand placement itself is not symmetric. Partially-ligated states can be populated sufficiently for experimental study only in negatively cooperative systems, which were not considered in the MWC model. The work reported here uses 1 H, 13 C, 15 N, and 19 F NMR to evaluate the structural symmetry of the hexameric arginine repressor of E. coli, a negatively cooperative system, with a single bound L-arginine ligand. The analysis indicates that the singly-ligated hexamer maintains structural symmetry as probed by these four NMR nuclei. The results are consistent with earlier molecular dynamics simulations suggesting that the global dynamics of the singly-ligated assembly are harnessed to maintain structural symmetry. The results extend MWC symmetry concepts to this negatively cooperative system, and indicate a role for global dynamics in allostery.